Education Abroad and the Character of Nationalism: A Case Study of Indonesian Students in Malaysia - Widodo, Syukri Fathudin Achmad; Nuryanto, Apri; Muflih, Betania Kartika; Harjanto, Chrisna Tri; Prasetya, Tri Adi (Jurnal Pendidikan Karakter, 2024)
Education abroad has become a choice for Indonesian students to get the best education. Malaysia is one of the most popular international education destinations among Indonesians. Thousands of Indonesian students have chosen Malaysia to gain academic experience. This study aims to reveal how the experience of studying abroad, especially in Malaysia, affects the nationalist views of Indonesian students. This research method uses a case study focusing on Indonesian students studying at the International Islamic University Malaysia. The data collection method uses a questionnaire to measure Nationalism and contribution to the country. Students studying abroad face challenges and opportunities that can affect their perspective as Indonesian citizens. Some things that can affect their perspective include the quality of education, employment opportunities with high wages, and excellent public facilities. The results of the data analysis show that Indonesian students in Malaysia have an increased sense of Nationalism even though they have good opportunities to stay in Malaysia. This research provides insights into how Nationalism grows even when living abroad. The results of this study can be the basis for the Indonesian government to design programs that can support education and employment opportunities for Indonesian students studying abroad. Researchers can conduct further research to comprehend the long-term impact of international education on the nationalistic views of Indonesian students.